2022
DOI: 10.3390/agronomy12112741
|View full text |Cite
|
Sign up to set email alerts
|

Weeds in Cereal Crop Rotations May Host Fusarium Species That Cause Fusarium Head Blight and Grain Weight Losses in Wheat

Abstract: Fusarium Head Blight (FHB) is one of the most common worldwide wheat and other small grain diseases. The infection is caused by Fusarium graminearum and other related species, which significantly reduce grain yield and contaminate grains with mycotoxins which are harmful for humans and animals. Fusarium pathogen survives the winter well in plant debris left on the field. Weeds around and within crops are alternative hosts of Fusarium fungi when an economically important host plant is not present. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This study compared the mycotoxin contamination potential among various Fusarium species obtained from different host plant groups, including weeds and Triticum . Previous data have indicated that Fusarium isolates from various host plants can produce FHB disease with differing severity [ 27 , 28 ]. Weeds often become a source of pathogens when there are no significant host plants nearby [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study compared the mycotoxin contamination potential among various Fusarium species obtained from different host plant groups, including weeds and Triticum . Previous data have indicated that Fusarium isolates from various host plants can produce FHB disease with differing severity [ 27 , 28 ]. Weeds often become a source of pathogens when there are no significant host plants nearby [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…An inoculation procedure was conducted on heads of the spring wheat cultivar ‘KWS Chamsin’ in 2019 at the Lithuanian Research Centre for Agriculture and Forestry in experimental fields. During mid-flowering, the main Fusarium pathogens responsible for Fusarium head blight (FHB), including F. avenaceum and F. graminearum , were isolated from the internal tissues of asymptomatic weeds and were used to inoculate the ears of spring wheat [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since triazole fungicides have been used for controlling different pathogens on crops for long periods, some Fusarium species showed tolerance to these chemicals [ 24 ]. Despite this, it is not clear how Fusarium strains isolated from alternative plants (weeds), which, in our previous studies, showed the ability to cause very intense FHB disease [ 6 ] produce mycotoxins [ 25 ] and reduce grain yield [ 26 ], respond to fungicides. Finally, it is valuable to monitor the sensitivity of Fusarium populations from different sources to fungicides as part of integrated disease and weed management to implement control strategies.…”
Section: Introductionmentioning
confidence: 99%